Komunikasi Pemasaran Destinasi Cagar Budaya di Kabupaten Lumajang - Fauziyah, Fauziyah; Pareno, Sam Abede (Jurnal Komunikasi Profesional, 2017)
Â Tourism is recently becoming excellent attraction for Indonesia development. Lots of Indonesia region have striven to develop its tourism destination in attracting more tourist, including Lumajang regency as one of potential destinations with several kinds of tourism object in East Java. One of those is the cultural heritage. Besides, culture and natural tourism object are something may not be missed. From these phenomenon, the writer would like to have research on topic Marketing Communication Cultural Tourism Destination In Lumajang District. It is based on great potency of cultural heritage in LumajangIn this research, the writer will apply qualitative method approach and integrated marketing communication theory. It is to understand the tourism marketing strategy of Lumajang cultural heritage. It is due to great potency of Archaeological sites in Lumajang which needs certain strategy in increasing the number of visitor.Tourism and Cultural Department of Lumajang as the manager needs to compile innovative and creative steps in marketing communication implementation. Tourism and Cultural Department of Lumajang, in fact, has not maximumly implemented that marketing communication at all. For intense, it concerns marketing target and even positioning which is so limited. It seriously will make government need to plan innovative marketing communication design and message as creative as possible. Therefore, I may influence tourist to visit Lumajang regency more. The results showed that the means of integrated marketing communication has not been applied as a whole so that required a very high commitment by the Government of Lumajang Regency, in this case the Department of Tourism and Culture of Lumajang Regency to apply it in an integrated manner in the years to come, in order to preserve the preservation Culture in Lumajang DistrictKeywords : Marketing Communication, Tourism Destination, Cultural Heritage Â Â